2001
DOI: 10.1136/heart.86.1.e4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carvedilol on left ventricular function, mass, and scintigraphic findings in isolated left ventricular non-compaction

Abstract: Tl and BMIPP uptake in the area of noncompaction observed before carvedilol disappeared after treatment. Impaired sympathetic neuronal function shown by MIBG recovered after treatment. Thus carvedilol had beneficial eVects on left ventricular function, hypertrophy, and both metabolic and adrenergic abnormalities in isolated left ventricular non-compaction. (Heart 2001;86:e4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 8 publications
(11 reference statements)
2
60
1
9
Order By: Relevance
“…10 The association of LVHT with embolism is in other's and our experience 11,12 not as high as previously reported. 7 Did the patient suffer from any embolic events during her lifetime?…”
Section: Uncertainties In Left Ventricular Hypertrabeculation/noncompcontrasting
confidence: 41%
“…10 The association of LVHT with embolism is in other's and our experience 11,12 not as high as previously reported. 7 Did the patient suffer from any embolic events during her lifetime?…”
Section: Uncertainties In Left Ventricular Hypertrabeculation/noncompcontrasting
confidence: 41%
“…14 The beneficial effects of the ␤-blocker carvedilol on left ventricular function, mass, and neurohormonal dysfunction in an infant with INVM have been described. 33 Because of the frequency of ventricular tachycardia and significant risk of sudden cardiac death and systemic embolism, assessment for atrial and ventricular arrhythmias by ambulatory ECG monitoring should be performed annually. As more information is gathered about NVM and risk of sudden cardiac death, implantable defibrillator technology may have an expanded role.…”
Section: Managementmentioning
confidence: 99%
“…Patients with LVNC are managed with neurohormonal blockade, diuretics, and cardiac resynchronization/defibrillator therapy according to standard clinical guidelines for systolic and diastolic dysfunction though there has been limited study validating their efficacy in this population. One case study found that carvedilol improved EF, left ventricular dimensions, and left ventricular mass in an infant with isolated LVNC [79]. In another study of 10 children, carvedilol was associated with stabilization or improvement in ventricular function in 7 patients [11].…”
Section: Managementmentioning
confidence: 97%